Oligarki Partai Politik dan Reduksi Doktrin Constituent Recall dalam Tata Laksana Demokrasi Perwakilan di Indonesia - Koroh, Yan Agustinus; Hage, Markus Yohanis; Yohanes, Saryono (Pusat Riset dan Inovasi Nasional, 2026)
The dominance of the political party elite (oligarchy) in Indonesia's representative democracy system has shifted the meaning and implementation of the constituent recall doctrine. Although Article 1 paragraph (2) of the 1945 Constitution affirms that sovereignty resides with the people, in practice the recall mechanism is not a constituent right, but rather the exclusive authority of political parties. This study uses a normative legal method with a legislative, conceptual, and comparative approach. The research data was obtained from primary legal materials (the 1945 Constitution, Law Number 2 of 2008 concerning Political Parties, Law Number 2 of 2011 on Amendments to Law Number 2 of 2008 on Political Parties, Law Number 7 of 2017 on General Elections, Law Number 17 of 2014 on the MPR, DPR, DPD, DPRD (MD3), as well as secondary legal materials in the form of books, scientific journals, and opinions of constitutional law experts. The results of the study show conceptual reduction, namely the transfer of the people's right to revoke the mandate of their representatives to the parties, and categorical reduction, namely the narrowing of the function of recall to an internal party disciplinary tool. The applicable regulations, particularly MD3 Law, give excessive privileges to political parties, thereby severing the substantive relationship between representatives and constituents. This study proposes a participatory and accountable constituent recall model, with the right of initiative in the hands of the people through public petitions, verification by an independent institution, and a final decision through a real election.